Analisis Kinerja Pegawai di Sekretariat Fraksi Partai Amanat Nasional Dewan Perwakilan Rakyat Republik Indonesia - Mutiara Berta; Nida Handayani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Employee performance is a benchmark for an organization or company in assessing the success of an organization. The Secretariat of the Pan Faction of the House of Representatives of the Republic of Indonesia is the main activity of the agency to evaluate the performance of employees and the board. There are problems in this study, namely errors in work, the amount of work that is overloaded because it is not supported by unbalanced human resources, then the problem of missed communication. The purpose of this study is to know and analyze how employees perform at the Secretariat of the Pan Faction of the House of Representatives. This study uses the theory of T.R. Mitchell (1978) in Sedarmayanti (2001) the indicators used in this study are service quality, communication, speed, ability, initiative. This research method uses qualitative descriptive techniques with data collection from interviews, observations and documentation. The results of this study show that the principle of service quality in employee performance pays attention to the servants provided in doing work. In the principle of communication, employees can easily carry out good communication so as to make it easy to be able to understand the goals and words given by employees, but there are still shortcomings in communication, namely missed communication. In principle, speed in doing work as a whole is good enough, where the work is carried out on a schedule that has been set in the planning. In principle, the ability of employees is able to use computer facilities well, but sometimes they are still not careful in their work, causing errors such as data input. Initiative in doing their respective jobs is quite good where employees do not procrastinate work, and help other teams in completing work.